Pengaruh Kepemilikan Manajerial dan Solvabilitas Bagi Financial Performance pada Perusahaan Industri Dasar dan Kimia - Noval Andriyanto; Ujang Suherman; Rengga Madya Pranata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial performance ref;ects the company’s ability, which is evident from the financial reports, wihc serve as aguide for decision-making by stakeholders. The purpose pf our study is to provide e,pirecal evidence on how managerial ownershif and company ability to meet is its obligations (solvability) can influencefinancial performance. The sample selection was carried out using purposive sampling,whilethe data analysis employed a multiple regression approach. Our researchfocuses on 14 basic and chemical industry companies listed on the Indonesia Stock Exchenge (BEI) during the period 2020-2024 as the object of study. This Result in the finding that managerial ownership has np effecton financial performance, but solvability has a negative impect on financial performance.